Untargeted metabonomics and TLR4/ NF-κB signaling pathway analysis reveals potential mechanism of action of Dendrobium huoshanense polysaccharide in nonalcoholic fatty liver disease - Deng, Guang-hui; Zhao, Chen-chen; Cai, Xiao; Zhang, Xiao-qian; Ma, Meng-zhen; Lv, Jia-hui; Jiang, Wen-li; Peng, Dai-yin; Wang, Yan-yan; Xing, Li-hua; Yu, Nian-jun (Frontiers in Pharmacology, 2024)
Nonalcoholic fatty liver disease (NAFLD) is marked by hepatic steatosis accompanied by an inflammatory response. At present, there are no approved therapeutic agents for NAFLD. Dendrobium Huoshanense polysaccharide (DHP), an active ingredient extracted from the stems of Dendrobium Huoshanense, and exerts a protective effect against liver injury. However, the therapeutic effects and mechanisms of action DHP against NAFLD remain unclear. DHP was extracted, characterized, and administered to mice in which NAFLD had been induced with a high-fat and high-fructose drinking (HFHF) diet. Our results showed that DHP used in this research exhibits the characteristic polysaccharide peak with a molecular weight of 179.935 kDa and is composed primarily of Man and Glc in a molar ratio of 68.97:31.03. DHP treatment greatly ameliorated NAFLD by significantly reducing lipid accumulation and the levels of liver function markers in HFHF-induced NAFLD mice, as evidenced by decreased serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), total cholesterol (TC) and total triglyceride (TG). Furthermore, DHP administration reduced hepatic steatosis, as shown by H&E and Oil red O staining. DHP also inhibited the Toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) signaling pathway expression, thereby reducing levels of hepatic proinflammatory cytokines. Besides, untargeted metabolomics further indicated that 49 metabolites were affected by DHP.These metabolites are strongly associated the metabolism of glycine, serine, threonine, nicotinate and nicotinamide, and arachidonic acid. In conclusion, DHP has a therapeutic effect against NAFLD, whose underlying mechanism may involve the modulation of TLR4/NF-κB, reduction of inflammation, and regulation of the metabolism of glycine, serine, threonine, nicotinate and nicotinamide metabolism, and arachidonic acid metabolism.